Equilibrio y carga plantar en diferentes técnicas de sentadilla - Mateus Teixeira Matos; Kailane Santos Alves; Victor Coswig; Thiago Mattos Frota de Souza; Christian Emmanuel Torres Cabido; Tatiana Acioli; Maria do Socorro Cirilo-Sousa; Felipe J Aidar; Caian Façanha; Fabiola Bertú; Saulo Fernandes Melo Oliveira; Claudio Oliveira Assumpção; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to analyze dynamic balance and plantar load in different squatting techniques, providing insights into the influence of these exercises in practitioners who incorporate weightlifting into their training routines. A sample of 21 subjects engaged in activities involving three squatting techniques: Back Squat (BS), Front Squat (FS), and Overhead Squat (OHS) was analyzed. Participants assumed a baseline posture and performed exercises with approximately 50% RM for each squatting technique. A plantar pressure measurement system was used to assess center of pressure (COP) displacement, peak pressure (PP), and plantar load in different regions of the foot. One-way Welch's ANOVA considering COP displacement, PP, and percentage of force for each foot region was measured. The results showed no significant effect of the squatting technique on COP trajectory during the exercises. However, a significant interaction was observed between the squatting technique and PP compared to the static balance situation. All three squats resulted in higher PP than static balance, with OHS exhibiting the highest values, followed by FS and BS. No significant differences were found between the squat techniques. These findings suggest that different squat techniques can influence plantar load, but do not affect the trajectory of the COP during the execution of the exercise. The heel region generated the greatest plantar load among the three squat techniques and should receive greater attention during the squat and its variations. This information can assist in prescribing exercises and developing more efficient training programs for weightlifters.